Lean Stability Case Studies—Leveraging Science- and Risk-Based Approaches to Enable Meaningful Phase Specific Pharmaceutical Stability Strategies - Eric Adamec; Yelizaveta Babayan; Bruno Catacchio; Angela Coon; Allison Dill; Mingkun Fu; Lars Gruenig; Cherokee Hoaglund Hyzer; Michael Lesslie; Megan McMahon; Donnie Pulliam; Fenghe Qiu; et al. (Journal of Pharmaceutical Innovation, 2021)
Purpose Lean stability is a science- and risk-based initiative which utilizes the enhanced understanding of drug substance and drug product physical and chemical characteristics to (1) reduce and optimize the design of standard stability protocols; (2) expedite the generation of stability data without impact to safety, efficacy, or quality of the product; and (3) decrease time to market for innovative drugs. Lean stability was introduced in the early 2000s [ICH: Guideline Q1A(R2) (2003), ICH: Guideline Q1D (2002)] followed by reduced stability protocols, focusing on the critical quality attributes and critical time points, being reported in the literature [Skrdla et al. (J Pharm Biomed Anal 50: 794–796, 2009)]. While the concept of lean testing is not entirely new, and it is currently a part of several regulatory guidances, it continues to evolve and gain acceptance of the industry and regulators. Methods In this review, twelve case studies are presented where stability data was collected during clinical, registration, and post-approval phases of the product development. Results Case studies summarize the lean stability testing design, the strategies applied during the regulatory filing and the outcomes of the regulatory filings. Conclusion The authors expect that the case studies presented in this review will increase the visibility of lean stability, facilitate overcoming of the existing challenges, and accelerate the global regulatory acceptance of lean stability practices in the industry.

Describing and Mapping Human-Induced Vegetation Change in the Australian Landscape - Richard Thackway; Robert Lesslie (Environmental Management, 2008)

Multi-Criteria Assessment of Tensions in Resource Use at Continental Scale: A Proof of Concept with Australian Rangelands - Michael J. Hill; Robert Lesslie; Randall Donohue; Paul Houlder; Jane Holloway; Jodie Smith; Kim Ritman (Environmental Management, 2006)